La construcción de un espectador cómplice desde el metateatro y la autoficción en "Doña Rosita, anotada" de Pablo Remón - Rodriguez Alonso, María (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Through his texts, Pablo Remón makes the spectator aware of being in front of a work of fiction. In such a way that the illusion constructed by Remón is immediately destroyed, revealing its condition of artifice, of pure convention. If this resource already appears in previous works by the author, such as El tratamiento or Barbádos etcetera, it will reach its maximum development in Doña Rosita, anotada, winner of the National Prize for Dramatic Literature 2021. The most evident metatheatrical strategy in Doña Rosita, anotada is the direct allusion to the creative process, artistic creation as a theme, as evidenced by the title of the play. The Annotator himself and his vicissitudes in the work of adapting a play are the subject of Doña Rosita, anotada. Consequently, the audience accepts that there is no desire on stage to imitate reality, but even to deform it as a way of accessing it. The implications of the rupture implied by the figure of the Annotator are directly addressed to the spectator: he will no longer be passive or limit himself to accept as true what is offered on stage, but will involve his own imagination and adopt a position in front of the disarticulated reality that the theater represents. In short, the Annotator as the metatheatrical axis of Doña Rosita, anotada dismantles the dramatic convention that dispensed with the enunciating figure typical of narrative and acts as an intermediate instance linking room and stage, inviting the spectator to complete the theatrical event.
Keywords: Metatheater; Autofiction; Spectator; Pablo Remón